2004
DOI: 10.1172/jci23235
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing islet transplantation for the treatment of type 1 diabetes mellitus

Abstract: Islet transplantation represents a most impressive recent advance in the search for a type 1 diabetes mellitus cure. While several hundred patients have achieved at least temporary insulin independence after receiving the islet "mini-organs" (containing insulin-producing β cells), very few patients remain insulin independent beyond 4 years after transplantation. In this review, we describe historic as well as technical details about the procedure and provide insight into clinical and basic research efforts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 90 publications
1
51
0
Order By: Relevance
“…The authors also reported that, BWithout further treatment, HbA 1c , and fasting glucose levels remained normal throughout the entire follow up of currently 4.5 years,'' and that serum autoantibodies to GAD65, IA-2, insulin, and ICA Bwere initially positive but showed a progressive decline or loss during follow-up.'' A similar case was recently reported by Rother and Harlan (15).…”
Section: Endocrine Pancreas Regeneration In Humanssupporting
confidence: 85%
See 2 more Smart Citations
“…The authors also reported that, BWithout further treatment, HbA 1c , and fasting glucose levels remained normal throughout the entire follow up of currently 4.5 years,'' and that serum autoantibodies to GAD65, IA-2, insulin, and ICA Bwere initially positive but showed a progressive decline or loss during follow-up.'' A similar case was recently reported by Rother and Harlan (15).…”
Section: Endocrine Pancreas Regeneration In Humanssupporting
confidence: 85%
“…Islet transplantation can be carried out under local anesthesia using a relatively simple and low-risk procedure that a larger number of potential recipients can tolerate safely. In light of the proven feasibility of islet transplantation in animals and autotransplantations to prevent diabetes in patients in whom the pancreas had to be surgically removed, approximately 750 patients with T1D received allogeneic islet transplants between 1974 and 2000 (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the promise of allogeneic islet transplantation has been hindered by immunologic damage and death from hypoxia, the requirement for post-transplant immunosuppression, and limited supply of pancreatic islets [64]. Even with improved protocols, long-term survival of the grafts is bleak, with most recipients requiring additional exogenous insulin therapy or a second transplant within a short time to meet their metabolic needs [65].…”
Section: Translational Imaging Of Transplanted Isletsmentioning
confidence: 99%
“…Recent advances in immunosuppressive regimens, beginning with a glucocorticoid-free therapy established by the Edmonton Group in Canada [51] and improved islet preparation techniques have meanwhile substantially contributed to the excellent long-term metabolic control in transplanted patients [46][47][48][49]. More than 750 patients have been treated so far, and further improvement of the immunosuppression protocols to reduce the risk of complications is one of the major future challenges [46,47].…”
Section: Introductionmentioning
confidence: 99%